Efeito do nitrato na descoloração redutiva de corante azo por lodo anaerobio mesofilico - Braúna, Carlos Henrique da Costa (2007)
The present investigation aimed to study the effect of nitrate on colour removal of dyes in anaerobic bioreactors supplemented or not with redox mediators. Two anaerobic bioreactors in parallel were operated at a hydraulic retention time (HRT) of 10 h, with ethanol as co-substrate. The contínuous flow experiment was divided in three steps after steady-state conditions were reached. In the first step, the reactors were fed with an affluent containing the azo dye Reactive Red 2 (RR2) tested in different concentrations. In the second step, one of the reactors was supplemented with the redox mediator AQDS, in order to evaluate its effect on the decolourisation process. Finally, in the third step of the experiment, both reactors (AQDS-supplemented and AQDS-free) received different concentrations of nitrate. The results showed that the reactors were efficient on colour removal, in which the compound ethanol was a good electron donor to sustain colour removal under anaerobic conditions. The redox mediator AQDS increased the decolourisation rates, but its effect was not so evident compared to the previous investigations. Contrary to the raised hypothesis that the nitrate addition could decrease decolourisation rates and catalytic properties of the redox mediators, no effect of nitrate was observed in the bioreactors, suggesting that the presence of nitrate in textile wastewaters will not decrease the capacity of anaerobic reactors supplemented or not with redox mediators to decolourize azo dyes. Finally, batch experiments evaluated the effect of an electron donor concentration gradient on colour removal, which indicated that the decolourisation rates were proportional to the concentration of ethanol tested and the redox mediator AQDS had a more evident effect on the colour removal kinetics.